THE INFLUENCE OF APPLICATION OF PRETREATMENT ON THE OSMOTIC DEHYDRATION OF APRICOTS - Ispir, Ayse; Togrul, Inci Turk (Wiley, 2009)
The synergistic effect of the application of pretreatment on osmotic dehydration was investigated. Various osmotic agents such as sucrose, glucose, fructose, maltodextrin and sorbitol, and different pretreatment solutions such as 5% Na2S2O5, 5% K2S2O5, 2% ethyl oleate (EO) + 5% Na2S2O5, 2% EO + 5% K2S2O5 and 5% K2CO3 were used. The application of EO + K2CO3 in maltodextrin and the use of EO + K2S2O5 and EO + K2CO3 in sorbitol showed the best positive effect. The application of EO + Na2S2O5, EO+ K2S2O5 and EO + Na2S2O5 in fructose, glucose and sucrose, respectively, showed better result than the other chemicals. Mass transfer was quantitatively investigated by means of effective diffusion and mass transfer coefficients. The effective diffusion coefficients for water and solid ranged from 0.857 x 10(-10) to 2.51 x 10(-10) m(2)/s, and from 0.75 x 10(-10) to 2.15 x 10(-10) m(2)/s, respectively. The mass transfer coefficients for water and solid were obtained as 1.041 x 10(-4) to 6.224 x 10(-4) (1/s), and 10.39 x 10(-4) to 1.043 x 10(-4) (1/s), respectively.
Keywords: Mass-Transfer; Fickian Diffusion; Drying Kinetics; Fruit; Coefficients; Stability; Exchange; Behavior; Potato; Sugars